The Politics of Alienation in Gary Shteyngart's Lake Success. Issue 3 (27th May 2021) - Naydan, Liliana M.
ABSTRACT: This article considers Gary Shteyngart's Lake Success as a literary exploration of alienation that is set against the backdrop of the 2016 presidential election in the United States. It exposes alienation as involving and also transcending immigrant identity, the central subject of most of Shteyngart's works. By putting Lake Success into conversation with Rahel Jaeggi's theory of alienation and American authors who comment on the subject, I argue that Shteyngart showcases its ubiquity and the ways in which self-alienation and social alienation relate to one another in the face of President Donald Trump's attempts to alienate and vilify immigrants and other diverse individuals in America. In the process, Shteyngart exposes missed opportunities for self-realization and invites America as a nation to subvert alienation and find success in and through its hybridity and diversity.